SP0074 Changing health behaviours with social marketing. (23rd January 2014) - Suarez-Almazor, M.
Abstract : Social marketing in health uses systematic commercial marketing techniques to promote the adoption healthy lifestyle behaviors and attitudes. Commercial advertising aims to increase the sales of a product by convincing potential buyers of the merits of its attributes. While a commercial ad campaign can be mostly based on the features of the product of interest (cognitive appeal), it often also engages viewers by appealing to their emotions, presenting situations or data that can trigger a desire to buy a given product (e.g. warm family scenes centered around the product). In social marketing, the overall goal is the adoption by the population of interest of behaviors leading to better health. A social marketing campaign goes beyond solely raising awareness of an issue, and attempts to bring about long-term health behavior changes. As in traditional marketing, social marketing campaigns are developed and implemented on the four P's strategy: Product, Price, Place, and Promotion. In social marketing, the Product presented most often is a behavior being encouraged, which often entails a change in lifestyle (e.g. exercise) or a change in healthcare use (e.g. screening). The Price to pay is not just monetary, it involves giving something up that is satisfying (e.g., smoking). Place refers to where and when to deploy the marketing message. People will not go out of their way, so the message must reach them where they can pay attention, and most importantly, in situations when they might be ready to make a decision or to change health habits (e.g. physician office). Finally, Promotion stands for the techniques and media used to disseminate the social marketing message. With the explosion of multimedia into everyday's life, newer media such as Web marketing and social networks are being increasingly explored. Given the increased recognition of the role of comorbidities on the outcomes of patients with rheumatic disease, attention to a healthy lifestyle, and behaviors promoting well-being, are of paramount importance. This presentation will discuss how social marketing strategies might be implemented to improve the overall health of patients with rheumatic disease. Disclosure of Interest: None Declared